KEBIJAKAN PAJAK DAERAH BERBASIS KEADILAN UNTUK MENDORONG PERTUMBUHAN USAHA KECIL MENENGAH (UKM) DI JAWA TENGAH - Amin Purnawan; Siti Ummu Adillah (Jurnal Pembaharuan Hukum, 2014)
Local taxes can be used as one means to support regional development. However, until now there has been realized harmonization between budgetary functions and regulerend functions in the area of tax collection, especially for SMEs. Taxation for SMEs can be a burden that affects its survival. Noteworthy aspects of justice fore tax burden for SMEs, even tax revenues should be used to encourage the growth of SMEs through training, capital, business facilities and so forth. Development of the area in the future design of tax policy needs to consider the ability to pay and the principle of benefit to raise taxes on SMEs.